2017
DOI: 10.1007/s00210-017-1424-x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants inhibit Nav1.3, Nav1.7, and Nav1.8 neuronal voltage-gated sodium channels more potently than Nav1.2 and Nav1.6 channels expressed in Xenopus oocytes

Abstract: Tricyclic antidepressants (TCAs) and duloxetine are used to treat neuropathic pain. However, the mechanisms underlying their analgesic effects remain unclear. Although many investigators have shown inhibitory effects of antidepressants on voltage-gated sodium channels (Na) as a possible mechanism of analgesia, to our knowledge, no one has compared effects on the diverse variety of sodium channel α subunits. We investigated the effects of antidepressants on sodium currents in Xenopus oocytes expressing Na1.2, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…It was also shown that the increased density of microglial cells and astrocytes correlates with pain hypersensitivity due to oxaliplatin administration [24], and decreased activation of the microglia and astrocytes relieved pain and stimulated neuroprotection [23,25]. Based on these findings [26][27][28][29][30][31][32][33], in this present research minocycline was used alone or in combination with a Na v channel inhibitor, i.e., ambroxol [34][35][36], or a serotonin/noradrenaline reuptake inhibitor with Na v -channel blocking properties, duloxetine [37,38], to attenuate tactile allodynia and cold hyperalgesia caused by oxaliplatin.…”
Section: Introductionmentioning
confidence: 67%
“…It was also shown that the increased density of microglial cells and astrocytes correlates with pain hypersensitivity due to oxaliplatin administration [24], and decreased activation of the microglia and astrocytes relieved pain and stimulated neuroprotection [23,25]. Based on these findings [26][27][28][29][30][31][32][33], in this present research minocycline was used alone or in combination with a Na v channel inhibitor, i.e., ambroxol [34][35][36], or a serotonin/noradrenaline reuptake inhibitor with Na v -channel blocking properties, duloxetine [37,38], to attenuate tactile allodynia and cold hyperalgesia caused by oxaliplatin.…”
Section: Introductionmentioning
confidence: 67%
“…Of note, lidocaine, carbamazepine, and amitriptyline have been reported to inhibit all the aforementioned Nav channel subtypes expressed by nociceptors. 30,34,[48][49][50] In addition, in corneal nociceptive nerve terminals, functional evidence suggests that tetrodotoxin-resistant sodium currents are the primary determinant of their excitability, 51 which leads to the presumption that tetrodotoxin-resistant sodium channels are the main contributors to the onset of membrane hyperexcitability in corneal nociceptive terminals after injury, and in turn they are the main molecular targets of the sodium channel blockers assessed in this work.…”
Section: Discussionmentioning
confidence: 96%
“…Amitriptyline is an antagonist of the histamine, muscarinic, adrenergic, and serotonin receptors, and leads to blockade of voltage-gated sodium ion channels 30,41 . It also appears to interact with calcium ion channels 37 .…”
Section: Introductionmentioning
confidence: 99%